Theoretical Simulation and Experimental Investigation of a Rail Damper to Minimize Short-Pitch Rail Corrugation. (11th April 2017) - Zhao, Caiyou; Wang, Ping; Sheng, Xi; Meng, Duo
Abstract : The Cologne-egg fastening systems applied in metro lines, which can be subjected to rail corrugation, are considered in this paper. To understand the mechanism of the formation and development of rail corrugation, dynamic models of the wheel and the track with Cologne-egg fastening system in the frequency domain are developed to analyse the wheel and track vibration behaviour. A field test is also analysed to verify the validity of the mechanism. Using these experimental and theoretical results, the vibration mode of the rail that is responsible for rail corrugation is determined. Based on the results, a novel rail damper that can suppress the track pinned-pinned resonance and smooth the track receptance is presented to minimize short-pitch rail corrugation. It is ultimately found from theoretical simulation and experimental investigation that the application of the rail damper is a long-term and effective method of controlling short-pitch rail corrugation in metro lines.